Intrinsic lubrication: A new approach in the context of the deep drawing process - Cakici, Ermir; Homberg, Werner (Materials Research Proceedings)
Abstract. This study presents intrinsic lubrication as a novel approach to deep drawing processes, using additively manufactured, lubricant-permeable tools to minimize lubricant consumption and improve efficiency. Two systems were evaluated: a passive system based on capillary action and gravity, and an active system using pumped delivery for precise, on-demand application. Experimental tests were conducted on micro-bores (0.2-0.5 mm) to demonstrate their suitability for lubricant transport. Smaller bores have excellent capillary action but are prone to clogging, while larger bores offer higher permeability. The passive system is resource-efficient but requires adjustments to counteract gravitational asymmetry. The active system provides consistent lubricant distribution but is more complex. These findings provide a basis for optimizing intrinsic lubrication systems.

Intrinsic production of metal-carbon fiber reinforced plastic hybrid shafts using vacuum-assisted resin transfer molding - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Ellouz, Manel; Kordisch, Thomas (Journal of Composite Materials)
Over the past decades, the importance of lightweight structures in the aircraft and automotive industries has steadily increased due to regulations aimed at reducing global warming. Work hardened steel alloys are commonly used for lightweight applications, but they face stability issues when the material thickness reaches certain thresholds. Fiber Reinforced Plastics (FRP) offer a viable alternative due to their high strength-to-weight ratio, but they are often expensive due to long production cycles and high material costs. A feasible solution lies in hybrid lightweight designs that utilize expensive FRP materials only in highly stressed areas, achieving a balance between low mass and acceptable cost. These hybrid structures are lighter than metal components and more cost-effective compared to fully FRP structures, without compromising mechanical properties. This study focuses on producing rotationally symmetrical hybrid structures using Resin Transfer Molding (RTM) combined with vacuum assistance in a single-stage process. The research examines the effects of injection pressure, mold temperature, and the interface between metal and FRP. The mechanical characterization of these hybrid structures was conducted to assess their performance under torsion, compression, and interlaminar shear strength (ILSS) loading conditions. The results indicate that hybrid designs can offer a lightweight alternative without compromising mechanical properties.

Introduction to the Ethics of Emerging Technologies - Reijers, Wessel; Thomas Young, Mark; Coeckelbergh, Mark

Investigating the kill cloud: information warfare, autonomous weapons & AI - Bhila, Ishmael (Digital War)
The “kill chain”—involving the analysis of data by human users of military technologies, the understanding of that data, and human decisions—has fast been replaced by the “kill cloud” that necessitates, allows, and exacerbates increased thirst for domination, violence against distant populations, and a culture of experimentation with human lives. This commentary reports an interdisciplinary discussion organised by the Disruption Network Lab that brought together whistleblowers, artists, and experts investigating the impact of artificial intelligence and other emerging technologies on networked warfare. Exposing the problematics of networked warfare and the kill cloud, their colonial overtones, effects on human subjects in real life, erroneous scientific rationalities, and the (business) practices and logics that enable this algorithmic machinery of violence. The conference took place from the 29th of November to the 1st of December 2024 at the Kunstquartier Bethanien in Berlin, Germany.
Keywords: autonomous weapons systems; algorithmic warfare; cloud computing; war on terror

Investigation failure behavior in the shear tensile test with respect to the arrangements of clinched joints - Wolf, Eugen; Brosius, Alexander (Materials Research Proceedings)
This paper focuses on the failure behavior of specimens with various configurations of clinched joints under shear tensile loading. The primary objective is to assess the influence of the joining direction and the spatial arrangement of clinched joints on their mechanical performance. A number of experiments was conducted, focusing on three clinched joints arranged in different configurations, each varying in terms of joining direction and spacing. These configurations were subjected to shear tensile tests, with force-displacement curves recorded for each sample to provide a detailed characterization of their structural response. The experimental findings indicate that the specific arrangement of the clinched joints, in terms of joining direction, has a marginal impact on the overall failure behavior. This suggests that intricate modifications to the joining direction are unnecessary to achieve improved mechanical performance in such applications. These results offer valuable insights for the design of clinched joint assemblies, indicating that simplified joining strategies may suffice without compromising structural integrity under shear loading.
Keywords: Joining; Sheet Metal; Clinching

Investigation failure behavior in the shear tensile test with variety of specimen stiffness - Wolf, Eugen; Brosius, Alexander (MATEC Web of Conferences)
This paper focuses on the failure behavior of clinched specimens with various stiffnesses under shear tensile loading. The primary objective is to assess the influence of the specimen stiffness with an arrangement of clinched joints. The specimen stiffness depends on several variables. In addition to the material selection, the specific choice of geometry and the design of the clinched joints must also be taken into account. A number of experiments was conducted to investigate the failure behavior of specimens with an arrangement of three clinched joints under shear tensile loading. These configurations were subjected to shear tensile tests, with force displacement curves recorded for each specimen to provide a detailed characterization of their structural response. The stiffness is modified by altering the specimen width, which has marginal impact on the maximum force. The experimental findings indicate that reducing the specimen stiffness results in a shift in the type of stress, with the failure behavior becoming increasingly influenced by bending stress. These results offer important insights for the design of clinched joint assemblies, indicating that it is feasible to achieve the desired properties by changing the specimen stiffness.
Keywords: Joining; Sheet Metal; Stiffness; Clinching

Investigation of local heat treatment strategies for a multi-range capable rivet and the influence on joint formation and load-bearing capacity - Holtkamp, Pia Katharina; Kappe, Fabian; Probst, Paula; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
To reduce CO 2 emissions, the industry, particularly in the mobility sector, focuses on lightweight vehicles with multi-material structures. As thermal joining processes are reaching their limits, mechanical techniques such as self-piercing riveting are being used. One innovative solution is the versatile self-piercing riveting process (V-SPR), which combines different material combinations with a multi-range rivet. 1 The joining process is divided into the piercing process and the forming process of the rivet head to the respective sheet thickness. The rivet shaft requires sufficient strength to punch through the punch-sided sheet, and sufficient ductility of the rivet head is required to form onto the punch-sided sheet. To achieve a combination of these requirements, local inductive heat treatment strategies are used for the rivet. To ensure reproducible rivet hardening, a specialised device has been developed for precise rivet positioning in the induction coil and the subsequent quenching process. The heat treatment differs in terms of hardening times and temperatures. In addition, the heat treatment is combined with a subsequent tempering process. The study aims to determine the resulting hardness distributions and microstructures of the rivet and to investigate the influence of different heat treatment strategies on joint formation and load-bearing capacities. The results show that a graded hardening profile has a positive effect on the spreading behaviour of the rivet foot and the forming behaviour of the rivet head. Furthermore, the load-bearing behaviour of the joints is increased.

Investigation of the impact of a rotationally superimposed punch stroke on the binding mechanisms of a clinched joint - Lüder, Stephan; Wolf, Eugen; Schmale, Hans Christian; Brosius, Alexander (MATEC Web of Conferences)
This paper examines the impact of a rotationally superimposed punch stroke on the binding mechanisms of clinched joints of aluminum sheets. As part of the development of a method for ensuring the versatility of clinching, an additional rotational movement of the punch was introduced as a control variable to influence friction in the mechanical joining process. The effect of rotational superimposition on the force-displacement curve of the clinching processes was investigated using four test variants with different kinematics. The primary objective was to evaluate the binding mechanisms that maintain the integrity of the clinched joint. To evaluate the force closure of the resulting joint, two testing methods were employed throughout the course of the research, non-destructive resistance measurement using four-wire sensing method and destructive torsion testing. A crucial factor influencing the efficacy of the process is surface cleanliness, as contaminants between joining partners can impede the effectiveness of the clinched joint. Therefore, all specimens were meticulously cleaned prior to experimentation. This method exhibits promising potential in creating clinched joints that align with the demands of flexible manufacturing environments.
Keywords: Joining; Sheet Metal; Tribology; Clinching

Is Tax Transfer Pricing Harmonization a Panacea? Real Effects of Global Tax Transparency and Standards Consistency - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren (The Accounting Review)

Islam II - Paul, Jürgen; Schneider, Irene; Kokew, Stephan; Malik, Jamal; Schulze, Fritz; Günther, Sebastian; Schrode, Paula; Rebstock, Ulrich; Gharaibeh, Mohammad; Würsch, Renate; Rudolph, Ulrich; Reichmuth, Stefan; et al.

Kausalität im Längsschnitt. Funktionen und Formen von weil, denn, deshalb, deswegen, nämlich und da in der Textproduktion vom 4. bis zum 6. Schuljahr - Topalovic, Elvira; Drepper, Laura; Blachut, Alisa (Semantische Phänomene lehren und lernen. Linguistische Berichte (LB))

KI außer Kontrolle - Hälterlein, Jens (AUSDRUCK - Das IMI-Magazin)

Kinder- und Jugendtheologie und Tradition. - Reis, Oliver (Was hat das mit zu tun? Zugange zur Tradition in der islamischen Religionspädagogik)

Kinderlyrik als soziale Praxis am Beispiel von Arne Rautenbergs Lyrikbänden Mut ist was Gutes (2023) und Sekundenfrühling (2023) - Jagdschian, Larissa Carolin (Arne Rautenbergs und die (Kinder-)Lyrik der Gegenwart)

Klagende Robben. Environmental Sound Art und das Problem der Anwaltschaft - Spieker, Jonas (Non*binär! Sound und Gender im Posthumanismus)

Kollegiales Feedback in der Hochschullehre - Osthushenrich, Judith (Praxishandbuch Hochschullehre II - Bewertung, Digitalisierung und Barrierefreiheit)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Kölner Vorherrschaft über Westfalen? Zu den Ambitionen der Erzbischöfe von Köln (1188–1220) - Schreckenberg, Carolin (775 – Westfalen. Das Buch. Eine Region wird gemacht)

Kommunale Wasserregime - Wasser und Macht in der europäischen Stadt 1300-1900

Komplexität beherrschen, Kreisläufe schließen: Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper
Im Rahmen des BMBF-Forschungsvorhabens KORESIL wurden entlang einer beispielgebenden Prozesskette für hybride Leichtbaustrukturen notwendige Forschungs- und Entwicklungsschwerpunkte ermittelt. Insbesondere die Steigerung der Ressourceneffizienz und die Unterstützung des Menschen im Kontext zukünftiger Arbeitsumfelder standen dabei im Mittelpunkt der Arbeiten. Hierauf aufbauend konnten Handlungsempfehlungen für Wirtschaft, Wissenschaft und Politik abgeleitet werden. Das Projekt KORESIL ist eingebettet in das Projektnetzwerk des Forschungs- und Technologiezentrums für ressourceneffiziente Leichtbaustrukturen – FOREL. Dieses Zentrum wurde im Jahr 2013 als BMBF-Leuchtturmprojekt eingerichtet und ist eine offene, unabhängige Plattform zur Entwicklung von Hightech-Leichtbausystemlösungen in Multi-Material-Design für die Mobilität der Zukunft. Ziel der Plattform ist die Unterstützung von Entwicklungsprojekten, die Vernetzung der Leichtbauforschung innerhalb Deutschlands und die Zusammenführung verschiedener Förderinitiativen.

Konzept und Wirkungen eines Lehrmoduls zur demokratischen Erarbeitung von Beurteilungskriterien in bildungswissenschaftlichen Seminaren des Lehramtsstudiums - Wehde, Janis

Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Krisen historischen Lernens. Zum historischen Lernpotenzial sprachlich-interaktionaler Krisen im Geschichtsunterricht. - Pilz, Franziska (Theorie und Empirie - ein unzertrennliches Paar? Tagung der Early Career Researcher der Konferenz für Geschichtsdidaktik in der Universität Bielefeld 2023)

Künstlerische Zusammenarbeit zwischen Ehekonvention und Sublimation. Hans Werner Henzes Bühnenschaffen mit Ingeborg Bachmann, W.H. Auden und Chester Kallman - Tumat, Antje ((Wahl-)Verwandtschaften.Gemeinschaftliches kulturelles Handeln)
A preference for music theatre works is characteristic of Hans Werner Henze's oeuvre, as is his close collaboration with famous 20th-century authors, who wrote the libretti for his music theatre works. This paper explores the artistic collaborations of Hans Werner Henze and Ingeborg Bachmann on the one hand and Henze, Chester Kallman and W.H. Auden on the other in the context of their joint operatic work, surviving correspondence and poetological essays. This is set against the backdrop of how personal relationships can influence collaboration in the performing arts. In both cases, the letters and biographical writings of the aforementioned working groups, read from a gender perspective and with regard to creativity, forms of relationship and artistic collaboration, point to a tension between potential and desired personal relationships, the confrontation with marriage as a conventional social framework and artistic collaboration as a long-term connection.

Künstliche Intelligenz - Überlegungen zum Einsatz von ChatGPT im Pädagogikunterricht aus Perspektive der Medienbildung - Engemann, Mario (Zeitschrift PädagogikUNTERRICHT)

Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung)

Langrezension zu Matthias Bau et al (Hg.) 'Vergessene Klassiker der Sprachwissenschaft? Zur Einführung und Erinnerung` - Markewitz, Friedrich (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft)

Lead-Free Ceramics in Prestressed Ultrasonic Transducers - Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias (Actuators)
Today’s ultrasonic transducers find broad application in diverse technology branches and most often cannot be replaced by other actuators. They are typically based on lead-containing piezoelectric ceramics. These should be replaced for environmental and health issues by lead-free alternatives. Multiple material alternatives are already known, but there is a lack of information about their technological readiness level. To fill this gap, a small series of prestressed longitudinally vibrating transducers was set up with a standard PZT material and two lead-free variants within this study. The entire process for building the transducers is documented: characteristics of individual ring ceramics, burn-in results, and free vibration and characteristics under load are shown. The main result is that the investigated lead-free materials are ready to use within ultrasonic bolted Langevin transducers (BLTs) for medium-power applications, when the geometrical setup of the transducer is adopted. Since lead-free ceramics need higher voltages to achieve the same power level, the driving electronics or the mechanical setup must be altered specifically for each material. Lower self-heating of the lead-free materials might be attractive for heat-sensitive processes.

Lehrkräftebildung in NRW: bildungsgerecht, digital, ko-konstruktiv. Ein standortübergreifendes bildungswissenschaftliches Seminarkonzept auf der Basis eines MOOCs - Endberg, Manuela; Bellenberg, Gabriele; Schulze-Uludasdemir, Johanna; Eickelmann, Birgit (Bildungsforschung und Bildungspraxis in der Metropole Ruhr. Schule und Lehrkräftebildung gemeinsam im regionalen Kontext entwickeln)

Lehrkräftekooperation und Digitalisierung. Digital-kooperative Arbeitsbeziehungen im Schulfach Erziehungswissenschaft - Engemann, Mario
Die Herausforderungen des digitalen Transformationsprozesses tangieren das öffentliche und private Leben – davon ist selbstredend auch die Schule und der Unterricht betroffen. Zugleich gilt die Lehrkräftekooperation als eine Möglichkeit, um gesellschaftlichen Herausforderungen in Schulen begegnen zu können. Davon ausgehend untersucht Mario Engemann die digital-kooperativen Arbeitsbeziehungen von Lehrkräften – exemplarisch am gymnasialen Schulfach Erziehungswissenschaft. Unter Rückgriff auf ein Mixed-Methods-Design beantwortet er die Frage, wie sich die Lehrkräftekooperation hinsichtlich der Digitalisierung in Formen, Gestaltung und Rahmenbedingungen darstellt. Die empirische Datenbasis der Arbeit bilden ein eigens unter Berücksichtigung bestehender Items zur Lehrkräftekooperation konzipierter quantitativer Fragebogen sowie Expert*inneninterviews mit Lehrkräften.
Keywords: Bildungsforschung; Medienpädagogik; Lehrerkooperation; Digitalisierung; Schulfach Erziehungswissenschaft

Leitfaden zur Entwicklung und Implementierung von Zertifikatsprogrammen zur Förderung studentischer Gesundheitskompetenzen - Sting, Anna-Lena; Kehne, Dennis; Wobbe, Lena; Waltert, Carolin (Gesundheitskompetenzen in Hochschulen entwickeln - Studierende für ihre berufliche Zukunft stärken)

Leitfaden zur Planung von Datenanalysen zur Entscheidungsunterstützung im Produktmanagement - Grigoryan, Khoren; Martin, Lucas; Fichtler, Timm; Reinhold, Jannik; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Vorausschau und Technologieplanung - 18. Symposium für Vorausschau und Technologieplanung)

Lerngegenstand, Modellierung, religionsdidaktisch - Reis, Oliver (WiReLex 02/2025)

Leveraging Self-Adaptive Systems and Generative AI for Personalizing Educational Serious Games: Architecture and Future Challenges - Bucchiarone, Antonio; Bonetti, Federico; Yigitbas, Enes (Proceedings of the 20th International Conference on Software Engineering for Adaptive and Self-Managing Systems (SEAMS 2025))

Lie groups of real analytic diffeomorphisms are L^1-regular - Glöckner, Helge (Nonlinear Analysis)
Let $M$ be a compact, real analytic manifold and $G$ be the Lie group of all real-analytic diffeomorphisms of $M$, which is modelled on the (DFS)-space ${\mathfrak g}$ of real-analytic vector fields on $M$. We study flows of time-dependent real-analytic vector fields on $M$ which are integrable functions in time, and their dependence on the time-dependent vector field. Notably, we show that the Lie group $G$ is $L^1$-regular in the sense that each $[\gamma]$ in $L^1([0,1],{\mathfrak g})$ has an evolution which is an absolutely continuous $G$-valued function on $[0,1]$ and smooth in $[\gamma]$. As tools for the proof, we develop several new results concerning $L^p$-regularity of infinite-dimensional Lie groups, for $1\leq p\leq \infty$, which will be useful also for the discussion of other classes of groups. Moreover, we obtain new results concerning the continuity and complex analyticity of non-linear mappings on open subsets of locally convex direct limits.

Linking social capital accumulation and information-seeking practices of international students in Germany - Teichert, Jeannine; Lin-Januszewski, Liang-Wen (Transitions: Journal of Transient Migration)
While existing studies have extensively explored various facets of international students’ experiences, a gap remains in understanding the connection between their social capital accumulation and information-seeking practices that shape the incoming students’ extended transition process. Successful information-seeking is not solely related to academic outcome; it is also influenced by the social capital resources available within and beyond familiar cultural groups. This article sheds light on how international students’ social capital accumulation shapes their information searches across various online and offline social networks. A total of ten international students were interviewed at the beginning and the end of their first semester in Germany during the 2022–23 academic year. The findings demonstrate that the incoming students’ information-seeking strategies and social capital accumulation change over time. The students rely on their previously established social connections offline and online when preparing for their departure. Upon arrival in Germany, the students continue to search for information within their linguistic and cultural familiar groups, but their information-seeking process shifts to local in-person contexts. During the semester, lecturers and fellow students become useful information sources at the university while the students develop confidence in their foreign language skills.

Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien - Maiterth, Ralf; Piper, Yuri; Sureth-Sloane, Caren (Steuer und Wirtschaft)
Dieser Beitrag untersucht Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien. Mithilfe von Daten einer Immobilien-Kapitalgesellschaft werden die Wirkungen einer Vermögensteuer auf die Cashflows aus der Vermietung von Wohnimmobilien simuliert. Der Detailgrad der Daten ermöglicht dabei Analysen auf Jahres-, Regional- und Baujahresebene. Ein Abgleich mit weiteren Immobiliendaten untermauert die Vergleichbarkeit und Aussagekraft der Analysen. Die Ergebnisse der Simulation zeigen, dass die Einführung einer Vermögensteuer den Cashflow aus dem Mietgeschäft erheblich reduzieren und zu Liquiditätsproblemen führen kann. Im Durchschnitt über alle Beobachtungen ergibt sich bei einem Vermögensteuersatz i.H.v. 2 % ein negativer Cashflow nach Berücksichtigung aller Kosten. Generell bedeutet dies, dass wachstumsorientierte Immobilien durch eine Vermögensteuer liquiditätsmäßig stärker belastet werden als mietrenditeorientierte Immobilien. Insbesondere in Großstädten mit hohen Immobilienwerten, aber verhältnismäßig geringen Mieten, können die Liquiditätseffekte mehr als dreimal so hoch ausfallen wie in ländlichen bzw. industriell-geprägten Regionen, was zu einem relativen Attraktivitätsverlust führen kann. Durch die Entkopplung der Vermögensteuer von den Mieterträgen zeichnet sich eine starke Abhängigkeit der Steuerlast von aktuellen Marktentwicklungen und dem Zinsumfeld ab, was eine zusätzliche Unsicherheit für Investoren darstellt. Diese steuerliche Unsicherheit könnte sich potentiell auf die Investitionsbereitschaft auswirken und sollte daher in politischen Diskussionen über die Wiedereinführung einer Vermögensteuer berücksichtigt werden.

Literarische Fiktionalität in der Vormoderne. Beiträge zu Problemen und Perspektiven

Locally homogeneous Axiom A flows II: geometric structures for Anosov subgroups - Delarue, Benjamin; Monclair, Daniel; Sanders, Andrew (arXiv:2502.20195)
Given a non-compact semisimple real Lie group $G$ and an Anosov subgroup $Γ$, we utilize the correspondence between $\mathbb R$-valued additive characters on Levi subgroups $L$ of $G$ and $\mathbb R$-affine homogeneous line bundles over $G/L$ to systematically construct families of non-empty domains of proper discontinuity for the $Γ$-action. If $Γ$ is torsion-free, the analytic dynamical systems on the quotients are Axiom A, and assemble into a single partially hyperbolic multiflow. Each Axiom A system admits global analytic stable/unstable foliations with non-wandering set a single basic set on which the flow is conjugate to Sambarino's refraction flow, establishing that all refraction flows arise in this fashion. Furthermore, the $\mathbb R$-valued additive character is regular if and only if the associated Axiom A system admits a compatible pseudo-Riemannian metric and contact structure, which we relate to the Poisson structure on the dual of the Lie algebra of $G$.

Logics with probabilistic team semantics and the Boolean negation - Hannula, Miika; Hirvonen, Minna; Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Virtema, Jonni (Journal of Logic and Computation)
Abstract We study the expressivity and the complexity of various logics in probabilistic team semantics with the Boolean negation. In particular, we study the extension of probabilistic independence logic with the Boolean negation, and a recently introduced logic first-order theory of random variables with probabilistic independence. We give several results that compare the expressivity of these logics with the most studied logics in probabilistic team semantics setting, as well as relating their expressivity to a numerical variant of second-order logic. In addition, we introduce novel entropy atoms and show that the extension of first-order logic by entropy atoms subsumes probabilistic independence logic. Finally, we obtain some results on the complexity of model checking, validity and satisfiability of our logics.

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.

Machine learning of continuous and discrete variational ODEs with convergence guarantee and uncertainty quantification - Offen, Christian (Mathematics of Computation)
The article introduces a method to learn dynamical systems that are governed by Euler–Lagrange equations from data. The method is based on Gaussian process regression and identifies continuous or discrete Lagrangians and is, therefore, structure preserving by design. A rigorous proof of convergence as the distance between observation data points converges to zero and lower bounds for convergence rates are provided. Next to convergence guarantees, the method allows for quantification of model uncertainty, which can provide a basis of adaptive sampling techniques. We provide efficient uncertainty quantification of any observable that is linear in the Lagrangian, including of Hamiltonian functions (energy) and symplectic structures, which is of interest in the context of system identification. The article overcomes major practical and theoretical difficulties related to the ill-posedness of the identification task of (discrete) Lagrangians through a careful design of geometric regularisation strategies and through an exploit of a relation to convex minimisation problems in reproducing kernel Hilbert spaces.

Machine-Learning basierte Analyse von latenten Profilen des physikdidaktischen Wissens Machine-Learning-Based Analysis of Latent Profiles in Physics PCK - Zeller, Jannis; Riese, Josef (Zeitschrift für Didaktik der Naturwissenschaften)
Das fachdidaktische Wissen (FDW) stellt eine wichtige Komponente des Professionswissens von (angehenden) Lehrkräften dar. Es liegen bereits empirische Forschungsergebnisse zu Einflussfaktoren und zur Entwicklung des FDW sowie zur Bedeutung des FDW als Ganzem für Professionswissen und Qualität professioneller Handlungen vor. Für eine detailliertere Forschung zur Zusammenhangsstruktur zwischen FDW und der Performanz in prototypischen Handlungssituationen sind darüber hinaus differenziertere empirisch begründete Beschreibungen der inneren Struktur des FDW notwendig. Bisher sind entsprechende Ansätze allerdings zumeist primär theoretisch-normativ begründet oder auf hierarchische Betrachtungen beschränkt. Im vorliegenden Beitrag wird daher ein Ansatz zur nicht-hierarchischen datenbasierten Beschreibung latenter Kompetenzprofile des FDW orientiert an der Computational Grounded Theory vorgestellt. Dabei wird zunächst mithilfe eines Datensatzes von 846 Bearbeitungen des Physik-FDW-Testinstruments in überwiegend offenem Antwortformat aus dem Projekt ProfiLe-P+ eine latente Profilanalyse zur Untersuchung latenter FDW-Profile unter Fokus auf kognitive Anforderungen als empirisch trennbare Subskalen des FDW durchgeführt. Mithilfe von Topic Modeling werden anschließend Tendenzen in der Sprachnutzung der FDW-Profile untersucht. Um die Ergebnisse im Sinne der Computational Grounded Theory durch den Nachweis latenter Zusammenhänge zwischen den Testantworten der Proband:innen und der FDW-Profil-Zuordnung zu bestätigen, wird im Anschluss ein Machine-Learning-basiertes System zur automatisierten Zuordnung von Testbearbeitungen zu den FDW-Profilen erstellt. Es zeigen sich vier latente Kompetenzprofile mit nicht-hierarchischem Charakter. In einer längsschnittlichen Betrachtung wird abschließend die Entwicklung von Proband:innen im Kontext dieser FDW-Profile dargestellt. Die Ergebnisse bieten Ansatzmöglichkeiten zukünftig Untersuchungen der Zusammenhänge einzelner FDW-Komponenten und beispielsweise gezeigter Handlungsqualität auf Detailebene zu untersuchen.

Maddy, Penelope, Jouko Väänänen, Philosophical Uses of Categoricity Arguments, Cambridge University Press: Cambridge 2023 (Cambridge Elements). - Peckhaus, Volker (zbMATH Open, Zbl. 07771690)

Mastering Temporal Challenges – Zeitwohlstand und Zeiterleben iranischer Studierender in Deutschland - Philipper, Matthias (Geschlecht und Gerechtigkeit)

Materialien zum Schreiben im Psychologieunterricht - Scharlau, Ingrid; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Mathematics education for girls in Prussia 1890–1925 - Krüger, Katja; Werth, Gerda (The Journal of Mathematical Behavior)

Mathematikbezogenes Wissen, Einstellungen und Lerngelegenheiten als Einflussfaktoren der situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachkräfte - Quack, Carolin; Bruns, Julia (Frühe Bildung)

Mathematische Grundbildung und rechnerische Grundkompetenzen im Feld der „Berufsbildung“ - Heisler, Dietmar; Sommer, Christian (Grundbildung und Habitus)
Zusammenfassung Für die Erklärung von sozialer Ungleichheit und des Einflusses sozialer Herkunft auf die Bildungsteilhabe von Individuen, auf ihre Bildungsbeteiligung und ihren Bildungserfolg wird oft auf die kultur- und bildungssoziologischen Ansätze Pierre Bourdieus zurückgegriffen. Dies gilt auch für den Bereich der Grundbildung, für die Erklärung von individuellen Leistungsunterschieden im Lesen, Schreiben und Rechnen. Unterschiede bei der Bildungsteilhabe und im Bildungserfolg werden von ihm u. a. auf die soziale Herkunft und die sozialen Praktiken in den sozialen Milieus zurückgeführt. Gerade Bourdieu versucht auch zu erklären, wie konkrete Anforderungen und Bildungsinhalte den Weg in schulische Curricula finden und so in Wechselwirkung mit den Strukturen des Bildungswesens und seinen sozialen Praktiken zur Reproduktion sozialer Ungleichheit in der Gesellschaft beitragen. Die These ist, dass die Inhalte und auch die Strukturen des Bildungswesens von einer bildungsnahen sozialen Oberschicht bestimmt werden, was den Bildungserfolg der Angehörigen dieser Schicht begünstigt und im Weiteren zur Reproduktion der Unterschiede zwischen den sozialen Milieus beiträgt. Der vorliegende Beitrag übersetzt dies in den Bereich der Grundbildung, vor allem der mathematischen Grundbildung und Vermittlung basaler mathematischer Grundkompetenzen. Ausgangspunkt ist die Frage, was unter mathematischer Grundbildung verstanden wird. Dafür wurden 21 Berufsschullehrkräfte in Interviews befragt. Die Ergebnisse der Befragung zeigen, dass mathematische Grundbildung von den Lehrkräften zu den Anforderungen von Bildungsgängen und Berufen kontextualisiert bzw. in Relation gesetzt wird. Als mathematische Grundkompetenzen werden Wissen und Fähigkeiten verstanden, die notwendig sind, um einen gegenwärtigen Bildungsgang bewältigen zu können, und die in vorangegangenen Bildungsgängen erworben wurden. Folglich werden mathematische Grundkompetenzen, die für die Bewältigung beruflicher Bildungsgänge notwendig sind, an den Klassenstufen im allgemeinbildenden Schulsystem festgemacht, deren Inhalte für den jeweiligen Bildungsgang als Voraussetzung oder grundlegend zur Bewältigung seiner Anforderungen und Inhalte betrachtet werden. Das hat zur Folge, dass es zum einen kein einheitliches Verständnis zu mathematischer Grundkompetenz bzw. sogenannten basalen Rechenfähigkeiten gibt. Vielmehr werden diese an unterschiedlichen Klassenstufen und Leistungsniveaus festgemacht. Unter Rückgriff auf die Überlegungen Bourdieus bedeutet dies zum anderen, dass die beruflichen Schulen die soziale und herkunftsbedingte Selektivität, die bislang vor allem am allgemeinbildenden Schulsystem kritisiert wird, über ihre Bildungsgänge fortschreiben, indem aus den Bildungsgängen heraus formale und inhaltliche Anforderungen formuliert werden, die den konkreten Bezug zu bestimmten Klassenstufen und Schulformen nehmen. Dies kann nun als Ausdruck oder Hinweis auf die Selektions- und Allokationsfunktion von Schule interpretiert werden. Allerdings erscheint es insofern kritisch, da die beruflichen Schulen seit ihren Reformen in den 1970er Jahren doch den Anspruch erheben, deutlich durchlässiger und weniger sozial selektiv zu sein als die allgemeinbildenden Schulen.

Maximizing the benefits of student-generated drawing for real-world problem solving - Schönherr, Johanna; Mayer, Richard E. (Contemporary Educational Psychology)

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, M.; Holtkamp, P.-K.; Hoyer, K.-P.; Kappe, F.; Yildiz, S.; Bobbert, M.; Meschut, G.; Schaper, M. (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
One of the most important strategies for reducing CO 2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Mee To in Science. Sexualisierte Diskriminierung und Gewalt an Hochschulen.

Mehrebenenannotation argumentativer Lerner*innentexte für die automatische Textauswertung - Rezat, Sara; Kilsbach, Sebastian; Michel, Nadine; Karabey, Rabia; Stahl, Maja; Wachsmuth, Henning (Zeitschrift für Angewandte Linguistik)

mei-friend: An Interactive Web-based Editor for Digital Music Encodings (1.2.0) - Goebl, Werner; Weigl, David M.; Plaksin, Anna Viktoria Katrin
This release contains two new major features and several smaller improvements: Extension of mei-friend's facilities for editorial mark-up through a re-worked annotation panel (now renamed to enrichment panel). Thanks to @annplaksin! See documentation at https://mei-friend.github.io/docs/advanced/markup/. Redevelopment of git integration for more stable and sustainable collaborative editing. For more information, please see CHANGELOG.md

Meine Schwangerschaft - so individuell wie ich! - Schneider, Tamara; Weber, Julia

Metaphors for explaining - a short guide - Scharlau, Ingrid; Porwol, Philip
Künstliche Intelligenz oder auch einfach Erklären - verwenden sie absichtlich oder unabsichtlich Metaphern. Diese Metaphern können beeinflussen, wie die Sprecher*innen und Hörer*innen über das Thema denken und wie sie handeln. So können beispielsweise Erklärmetaphern beeinflussen, wie Wissenschaftler*innen erklärende technische Systeme entwerfen. Dieser Artikel soll die Aufmerksamkeit auf Metaphern und ihre möglichen Folgen lenken. Darüber hinaus beschäftigen wir uns mit verbreiteten spezifischen Erklärungsmetaphern beschäftigen und machen Vorschläge , welche Metaphern zum Verständnis des Erklärens im Rahmen des Sonderforschungsbereichs „Constructing Explainability“ passen bzw. nicht passen und was bei der Verwendung von Metaphern zu beachten ist.

Metaphors in 24 WIRED Level 5 Videos (Data corpus) - Scharlau, Ingrid

Metatextuelle Textprozeduren: Gliedern und Zusammenfassendes Wiedergeben. - Rezat, Sara; Feilke, Helmuth (Zusammen:gedacht. Transdisziplinäe Perspektiven auf Literalität und Schreiben im Kontext von Mehrsprachigkeit. Festschrift für Sabine Schmölzer-Eibinger.)

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Beule, Felix; Possart, Gunnar; Teutenberg, Dominik; Mergheim, Julia; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Mit dem Tandem durch die Wende – Aufbau der Benachteiligtenförderung in den neuen Bundesländern - Lippegaus, Petra; Schlegel, Wolfgang; Voigt, Birgit (Geschichten, die die Wende schrieb. Biografien, Erzählungen, Interviews)

MO-IOHinspector: Anytime Benchmarking of Multi-objective Algorithms Using IOHprofiler - Vermetten, Diederick; Rook, Jeroen; Preuß, Oliver Ludger; de Nobel, Jacob; Doerr, Carola; López-Ibáñez, Manuel; Trautmann, Heike; Bäck, Thomas (Evolutionary Multi-Criterion Optimization - 13th International Conference, EMO 2025, Canberra, ACT, Australia, March 4-7, 2025, Proceedings, Part I)

MO-SMAC: Multi-objective Sequential Model-based Algorithm Configuration - Rook, Jeroen G.; Benjamins, Carolin; Bossek, Jakob; Trautmann, Heike; Hoos, Holger H.; Lindauer, Marius (Evolutionary Computation)

Modeling and optimization of energy system components equipped with phase change materials - Grabo, Matti
Diese Arbeit behandelt die Modellierung und Optimierung von mit Phasenwechselmaterialien (PCM) ausgestatteten, energietechnischen Komponenten anhand zweier Fallstudien. PCM sind Materialien, deren Phasenwechseleigenschaften während des Schmelzens und Erstarrens für Heiz- und Kühlzwecke genutzt werden. Zunächst werden die theoretischen Grundlagen zu Wärmeübertragungsproblemen mit Phasenwechsel erörtert und entsprechende numerische Lösungsmethoden diskutiert. Ein Modell für Phasenwechselvorgänge wird vorgestellt, welches anhand analytischer Lösungen validiert wurde und in den Fallstudien zum Einsatz kam. Für beide Fallstudien wird der Stand der Technik erörtert und die entsprechenden Forschungsfragen werden formuliert. Die erste Fallstudie behandelt PCM-integrierte Photovoltaikmodule und die zweite Festbett-Latentwärmespeicher, welche nicht-kugelförmiger PCM-Kapseln verwenden. Für beide Systeme wurden thermische Model-le entwickelt und anhand experimenteller Daten mit guter Genauigkeit validiert. Diese Modelle wurden in Parameterstudien eingesetzt, um optimierte Systemkonfigurationen zu identifizieren. Die vorgestellten Ergebnisse zeigen, dass ein PCM-Kühlkörper mit ausreichender Dicke und Wärmeleitfähigkeit den Wirkungsgrad und die Lebensdauer von Photovoltaikmodulen erheblich erhöht. Darüber hinaus verbessern PCM-Kapseln mit hoher Packungs-dichte und Oberfläche sowohl die volumenspezifische Speicherkapazität als auch die thermische Leistung von Festbett-Latentwärmespeichern.
Keywords: Heat transfer; PCM; numerical simulation; renewable energy; heat storage

Modeling reactive absorption in sandwich packings - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Proceedings of the Dechema/VDI Jahrestreffen Fluidverfahrenstechnik 2025)

Modelling of stress-state-dependent ductile damage with gradient-enhancement exemplified for clinch joining - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (Journal of the Mechanics and Physics of Solids)
A coupled finite plasticity ductile damage and failure model is proposed for the finite element simulation of clinch joining, which incorporates stress-state dependency and regularisation by gradient-enhancement of the damage variable. Ductile damage is determined based on a failure indicator governed by a failure surface in stress space. The latter is exemplary chosen as a combination of the Hosford–Coulomb and Cockcroft–Latham–Oh failure criteria for the high and low stress triaxiality range, respectively, to cover the wide stress range encountered in forming. Damage is coupled to elasto-plasticity to capture the damage-induced degradation of the stiffness and flow stress. This affects the material behaviour up to failure, thereby realistically altering the stress state. Consequently, especially for highly ductile materials, where substantial necking and localisation precede material fracture, the failure prediction is enhanced. The resulting stress softening is regularised by gradient-enhancement to obtain mesh-objective results. The analysis of a modified punch test experiment emphasises how the damage-induced softening effect can strongly alter the actual stress state towards failure. Moreover, the impact of successful regularisation is shown, and the applicability of the damage and failure model to clinch joining is proven.
Keywords: Finite plasticity; Ductile damage; Gradient-enhancement; Stress-state dependency; Failure

Modelling strategies for non-rotationally symmetric joints - Devulapally, Deekshith Reddy; Tröster, Thomas (Materials Research Proceedings)
Abstract. Accurate Finite Element Modeling (FEM) of joints is essential in the design of complex mechanical systems such as automotive body-in-white (BIW) structures, as it plays a critical role in evaluating their performance. Although well-established techniques exist for modeling rotationally symmetric joints, there remains a significant gap in effectively modeling non-rotationally symmetric joints. These joints are particularly relevant in the automotive BIW, where they can better accommodate anisotropic loading conditions. In this study, strategies for modeling non-rotationally symmetric joints were explored using finite element simulations in LS-DYNA. The findings demonstrate that discrete beam elements can capture the anisotropic characteristics of such joints. Two models were tested: a single-beam model for stiffness periodicity every 90°, and a three-beam model for stiffness periodicity every 120°. Force responses, stress distribution, and sheet bending behaviors were analyzed, confirming that discrete beam elements can accurately represent direction-dependent stiffness. These results establish a foundation for developing advanced joint modeling strategies in complex mechanical systems.

Monitoring phage infection and lysis of surface-immobilized bacteria by QCM-D - Pothineni, Bhanu K.; Probst, René; Kiefer, Dorothee; Dobretzberger, Verena; Barišić, Ivan; Grundmeier, Guido; Keller, Adrian (Analytical and Bioanalytical Chemistry)
Abstract While being a promising approach for the treatment of infections caused by drug-resistant, pathogenic bacteria, the clinical implementation of phage therapy still faces several challenges. One of these challenges lies in the high strain-specificity of most bacteriophages, which makes it necessary to screen large phage collections against the target pathogens in order to identify suitable candidates for the formulations of personalized therapeutic phage cocktails. In this work, we evaluate the potential of quartz crystal microbalance with dissipation monitoring (QCM-D) to identify and detect phage infection and subsequent lysis of bacteria immobilized on the surfaces of the QCM-D sensors. Using lytic Escherichia coli phage T7 as a model, we show that phage infection of E. coli cells results in various unique alterations in the behaviors of the frequency (Δ f ) and dissipation (Δ D ) signals, which are not observed during exposure of the E. coli strain to non-infectious Bacillus subtilis phage phi29 at similar concentration. To aid future phage screening campaigns, we furthermore identify a single measurement parameter, i.e., the spread between the different overtones of Δ D , that can be used to detect phage-induced lysis. For T7 infection of E. coli , this is achieved within 4 h after inoculation, including immobilization and growth of the bacteria on the sensor surface, as well as the completed phage propagation cycle. Given the commercial availability of highly automated multichannel systems and the fact that this approach does not require any sensor modifications, QCM-D has the potential to become a valuable tool for screening medium-sized phage collections against target pathogens. Graphical Abstract

Moon, Stella S., “Demarcating Descartes’s Geometry with Clarity and Distinctness”, Synthese 202 (2023), No. 4, Paper No. 124, 29 pp. - Peckhaus, Volker (Mathematical Reviews, MR4654178)

More money or better procedures? Evidence from an Energy Efficiency Assistance Program - Chlond, Bettina; Goeschl , Timo; Kesternich, Martin (Journal of Environmental Economics and Management)

Muhammad as a Prophet of Late Antiquity: The Anti-Apocalyptic Nature of Muhammad’s Prophetic Wisdom - Ghaffar, Zishan (Theology of Prophecy in Dialogue: A Jewish-Christian-Muslim Encounter)

Multiphoton, multimode state classification for nonlinear optical circuits - Kopylov, Denis; Offen, Christian; Ares, Laura; Wembe Moafo, Boris Edgar; Ober-Blöbaum, Sina; Meier, Torsten; Sharapova, Polina; Sperling, Jan
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which being in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.

Musik und Arbeit
Der Band versammelt Beiträge zum vielgestaltigen Verhältnis von 'Musik' und 'Arbeit'. Zum einen wird Musik als Arbeit betrachtet, wobei Phänomene musikalischer Berufstätigkeit seit dem Mittelalter ebenso in den Blick geraten wie aktuelle Themen, etwa die Situation der Kreativwirtschaft im Kontext pandemischer Krisen. Zum anderen widmen sich die Fallstudien 'Arbeit' als Gegenstand oder Thema in Musik, so beispielsweise der musikalischen Nachahmung von Arbeitsprozessen und -geräuschen oder der musiktheatralen Darstellung der Arbeitswelt. Der Band versteht sich als eine Anregung für eine musikwissenschaftliche Auseinandersetzung mit dem Thema, aber auch für einen soziologischen Anschluss an musikbezogene Forschung.

Musik und Arbeit - Arbeit in der Musik. Einführende Überlegungen - Höink, Dominik; Feldhordt, Philip (Musik und Arbeit)

Musikalische Alltagskultur im Vormärz - Tumat, Antje; Korbmacher, Melissa Maria (Alltagskultur im Vormärz)

Muster in der Benamung 'nachhaltiger' Lebensmittelmarkennamen - Kulturbezogene Deutungen von Namen am stationären Verkaufsort als Raum - Dübbert, Alexander (Transdisziplinäre Räume in den Kulturwissenschaften)

Nachträgliche Gegenwart. Zur Rezeption Paul Celans in Frédéric Brenners "ZERHEILT" - Spener, Anna Maria (Celan-Perspektiven 5: Transformationen Celans in der Kunst der Gegenwart)

Neue Perspektiven der Unternehmensgeschichte [New Perspectives in Business History]: Edited by Nina Kleinöder, Christian Marx, Boris Gehlen, Juliane Czierpka, Brill/Schöningh, Paderborn, 2024 - Staffel, Florian (Business History)

Neural Network Inference in High-Performance Computing: Closing the Gap for FINN based Reconfigurable Accelerators - Jungemann, Linus; Wintermann, Bjarne; Riebler, Heinrich; Plessl, Christian (Proceedings of the 2025 ACM/SIGDA International Symposium on Field Programmable Gate Arrays)

Non*binär! Sound und Gender im Posthumanismus

Non*binäre Verflechtungen: Feministische Klangspaziergänge im Garten posthumanistischer Theoriebildung - Spieker, Jonas; Bartsch, Cornelia; Schürmer, Anna (Non*binär! Sound und Gender im Posthumanismus)

Non-destructive testing in versatile joining processes - Lechner, M.; Borgert, Thomas; Busch, Matthias; Harms, A.; Holtkamp, Pia Katharina; Römisch, D.; Wituschek, Simon; Kappe, Fabian (Materials Research Proceedings)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT's application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysis.

Non/Repeat: Three Case Studies of Non-linear Live-Music Practices - Kallionpää, M.; Berndt, Axel; Mauro, D.~A.; Dziwis, D. ({AM.ICAD: Audio Mostly & ICAD Joint Conf.})

Nonreciprocal Metasurfaces with Epsilon-Near-Zero Materials - Mathew, Albert; Aschwanden, Rebecca; Tripathi, Aditya; Jangid, Piyush; Sain, Basudeb; Zentgraf, Thomas; Kruk, Sergey (Nano Letters)

Normative Grundlagen des pluralistischen Paradigmas - Haker, Christoph (Kieler sozialwissenschaftliche Revue. Internationales Tönnies-Forum)

Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber contents - Wippermann, Jan; Meschut, Gerson (Welding in the World)
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental dynamical mechanical analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. An FE model is created and verified by substrate stress relaxation tests. Experimental clamp load measurements with miniature compression load cells verify the clamp load prediction and show a good agreement. The developed model is used to analyze the clamp load distribution within the threads and reveals an almost even distribution within the threads.

Nur Gewinner und Verlierer in der Erzählung vom Krieg? Der Zweck von Emotionen in den Beschreibungen der englischen Barons’ Wars (1216–1217 und 1264–1265) - Bröker, Christina (Emotionen im Krieg – Krieg der Emotionen)

On "Super Likes" and Algorithmic (In)Visibilities: Frictions Between Social and Economic Logics in the Context of Social Media Platforms - Schulz, Christian (Digital Culture & Society)

On matrices commuting with their Frobenius - Gundlach, Fabian; Seguin, Beranger Fabrice (arXiv:2506.08695)
The Frobenius of a matrix $M$ with coefficients in $\bar{\mathbb F}_p$ is the matrix $σ(M)$ obtained by raising each coefficient to the $p$-th power. We consider the question of counting matrices with coefficients in $\mathbb F_q$ which commute with their Frobenius, asymptotically when $q$ is a large power of $p$. We give answers for matrices of size $2$, for diagonalizable matrices, and for matrices whose eigenspaces are defined over $\mathbb F_p$. Moreover, we explain what is needed to solve the case of general matrices. We also solve (for both diagonalizable and general matrices) the corresponding problem when one counts matrices $M$ commuting with all the matrices $σ(M)$, $σ^2(M)$, $…$ in their Frobenius orbit.

On the association scheme of perfect matchings and their designs - Klawuhn, Lukas-André Dominik; Bamberg, John
We investigate generalisations of 1-factorisations and hyperfactorisations of the complete graph $K_{2n}$. We show that they are special subsets of the association scheme obtained from the Gelfand pair $(S_{2n},S_2 \wr S_n)$. This unifies and extends results by Cameron (1976) and gives rise to new existence and non-existence results. Our methods involve working in the group algebra $\mathbb{C}[S_{2n}]$ and using the representation theory of $S_{2n}$.

On the impact of various mobility concepts on integrated energy systems - Meschede, Henning; Knorr, Lukas (e-Prime - Advances in Electrical Engineering, Electronics and Energy)

On the variational discretization of optimal control problems for Lagrangian dynamics - Konopik, Michael; Leyendecker, Sigrid; Maslovskaya, Sofya; Ober-Blöbaum, Sina; de Almagro, Rodrigo T. Sato Martin
Abstract We derive the necessary optimality conditions of an optimal control problem with dynamical constraints described by forced Euler-Lagrange equations, using a recently proposed new Lagrangian approach [1] and use variational integrators to solve them. We show that for a family of low-order discretizations the resulting numerical schemes are ‘doubly symplectic’, meaning they provide forced symplectic integrators for the underlying controlled mechanical system and symplectic integrators in the state-adjoint space. This paves the way for variational error analysis to be used in the optimal control setting to derive the order of convergence of the resulting numerical schemes and further the possibility to apply discrete Noether’s theorem for the calculation of conserved quantities there. The schemes derived behave well numerically, benefiting from this ’double-symplecticity’. A multi-body example is solved and the benefits of this ‘double-symplecticity’ illustrated. The example demonstrates the convergence and also the ability to preserve first integrals associated to symmetries in the considered optimal control problem. Mathematics Subject Classification: 37M15, 49K15, 49M05, 49M25, 65K10, 65P10, 70H15, 70G45, 70G65, 70Q05.

On the Dynamical Hierarchy in Gathering Protocols with Circulant Topologies - Gerlach, Raphael; von der Gracht, Sören; Dellnitz, Michael (Lecture Notes in Computer Science)

One size fits all? Annäherungen an Leitlinien zum Transfer in Rahmen von Innovationsprogrammen - Daniel-Söltenfuß, Desiree; Kremer, H.-Hugo; Kückmann, Marie-Ann (Berufsbildungsforschung. Rezeption - Translation - Transfer)

Open Space. Der Raum als Mikroformat.

Optically and remotely controlling localization of exciton-polariton condensates in a potential lattice - Ai, Qiang; Wingenbach, Jan; Yang, Xinmiao; Wei, Jing; Hatzopoulos, Zaharias; Savvidis, Pavlos G.; Schumacher, Stefan; Ma, Xuekai; Gao, Tingge (Physical Review Applied)

Optimal transport of stationary point processes: Metric structure, gradient flow and convexity of the specific entropy - Erbar, Matthias; Huesmann, Martin; Jalowy, Jonas; Müller, Bastian (Journal of Functional Analysis)

Optimizing Injection Molding Tool Design with Additive Manufacturing: A Focus on Thermal Performance and Process Efficiency - Chalicheemalapalli Jayasankar, Deviprasad; Tröster, Thomas; Marten, Thorsten (Materials)
Injection molding plays a pivotal role in modern manufacturing, enabling the mass production of complex components with high precision. However, traditional tooling methods often face challenges related to thermal management, design constraints, and material efficiency. This study examines the use of additive manufacturing (AM) in the development and optimization of injection molding tools to overcome these limitations. A novel prototype was fabricated using AM techniques, incorporating integrated cooling channels and optimized lattice structures to enhance thermal performance and simplify the manufacturing process. Experimental validation demonstrated the prototype’s effective integration into a vacuum-assisted resin transfer molding (VA-LRTM) system without requiring modifications to existing tooling setups. The results showed significant improvements in temperature regulation, reduced cycle times, and consistent mechanical properties of the molded components compared to conventional approaches. By reducing the number of tool components and eliminating the need for support structures during manufacturing, AM also minimized material waste and post-processing requirements. This research highlights the transformative potential of additive manufacturing in injection molding tool design, offering increased flexibility, cost efficiency, and enhanced functionality to meet the evolving demands of modern industrial applications.

Otfried Preußlers Lyrik während der Kriegsgefangenschaft im Zweiten Weltkrieg - Jagdschian, Larissa Carolin (Otfried Preußler)

Oxygen‐dependent Photoluminescence and Electrical Conductance of Zinc Tin Oxide (ZTO): A Modified Stern‐Volmer Description - Kothe, Linda; Klippstein, Josefin; Kloß, Marvin; Wengenroth, Marc; Poeplau, Michael; Ester, Stephan; Tiemann, Michael (ChemPhysChem)
Zinc tin oxide (ZTO) is investigated as a photoluminescent sensor for oxygen (O2); chemisorbed oxygen quenches the luminescence intensity. At the same time, ZTO is also studied as a resistive sensor; being an n‐type semiconductor, its electrical conductance decreases by adsorption of oxygen. Both phenomena can be exploited for quantitative O2 sensing. The respective sensor responses can be described by the same modified Stern‐Volmer model that distinguishes between accessible and non‐accessible luminescence centers or charge carriers, respectively. The impact of the temperature is studied in the range from room temperature up to 150 °C.